Epidermal polymeric immunoglobulin receptors: leads from intraepidermal neutrophilic IgA dermatosis‐type IgA pemphigus. Issue 3 (March 2015) - Tsuchisaka, Atsunari; Ishii, Norito; Hamada, Takahiro; Teye, Kwesi; Sogame, Ryosuke; Koga, Hiroshi; Tsuruta, Daisuke; Ohata, Chika; Furumura, Minao; Hashimoto, Takashi
Abstract In this study, we attempted to identify unknown autoantigen for intraepidermal neutrophilic IgA dermatosis‐type IgA pemphigus by novel IgA‐specific immunoprecipitation. Mass‐spectrometry study identified polymeric immunoglobulin receptor (PIGR) as the candidate protein, and we confirmed that PIGR expressed in both epidermis and cultured keratinocytes. Eukaryotic recombinant protein of PIGR expressed in COS7 cells was reacted with both patient and normal sera, indicating that PIGR binds physiologically to IgA. To detect antigen‐specific binding by IgA autoantibodies, we performed several experiments using deglycosylated PIGR and F(ab)2 fragments from patient sera. However, these analyses suggested that patient IgA bound physiologically, but not immunologically, to PIGR. Nevertheless, our study provided two important insights. Newly developed IgA‐immunoprecipitation system should be a useful tool in the future study of identification of antigens for IgA autoantibodies. Detection of epidermal PIGR in this study confirmed previous results and indicated possible immunological role of PIGR in epidermis.